Implementasi Media Pembelajaran Berbasis 5E Cycle Berbantuan Scratch untuk Meningkatkan Physics Identity Siswa pada Materi Energi Terbarukan - Nugroho, Lucky Adi; Riki Perdana; Febrina Siska Widyaningtyas (JPUS: Jurnal Pendidikan Untuk Semua, 2026)
Low student achievement in physics indicates the need for instructional media that align with learners’ characteristics and learning needs. This study aims to develop an interactive physics learning medium based on the 5E learning cycle model using a three-dimensional Scratch application to enhance students’ learning outcomes on the topic of renewable energy. The research employed a research and development method with a 4D model consisting of defining, designing, developing, and disseminating stages. Data was collected using a validation questionnaire assessing content validity, construct validity, media aspects, pedagogical aspects, and readability. Five pre-service physics teachers participated as expert validators. The results showed an average validity score of 3.56, categorized as highly valid. These findings indicate that the Scratch-based learning medium is feasible and effective for fostering conceptual understanding and strengthening students’ physics identity through engaging and interactive learning experiences. Keywords: Renewable Energy, Learning Media, Scratch, 5E Model, Physics Identity